Analisis Biaya Produksi Syana Busana Klaten - Fatimah Mutia Shela; Mutia Miftahul Jannah; Fatimah Az-Zahro; Noor Laila Fitriana (Jurnal Manajemen Bisnis Syariah, 2024)
This study aims to determine the cost of production of Syana Busana Convection. Convection business has an important role in the textile and fashion industry, especially in producing apparel and other textile products. The cost structure in producing all products at Syana Busana Convection is very complex. Production costs include raw material costs, labor costs, factory overhead costs, distribution, and others. The research method includes direct interviews with the business owner of Syana Busana Convection. The result of this research is a deeper understanding of the cost of production of Syana Busana Convection. By knowing the cost of goods produced, it is hoped that it will make it easier to determine the selling price of each product.